DETEKSI FINANCIAL STATEMENT FRAUD: PENGUJIAN FRAUD DIAMOND PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Rakhmi Ridhawati; Mega Andani; Mellani Yuliastina; Jadidah Jadidah (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2021)
The purpose of this study was to prove and analyze Fraud Financial Statement Detection with Fraud Diamond Testing in Manufacturing corporations in the consumer goods industry sector listed on the IDX in the 2016-2018 period. This research used quantitative methods. The population of this study was manufacturing corporations in the consumer goods industry sector listed on the IDX in the 2016-2018 period. The sample of this study was 37 companies with a total of 111 data. The results of this study indicate that financial targets has no effect on financial statement fraud. External pressure has no effect on financial statement fraud. The nature of the industry has an effect the financial statement fraud. The ineffectiveness of supervision has no effect on financial statement fraud. The change of auditors has no effect on the financial statement fraud. Change of directors has no effect on financial statement fraud. Simultaneously, financial objectives, external pressures, the nature of the industry, ineffective supervision, turnover of auditors, and changes in directors has an impact on financial statement fraud.